(3CQLhRI eMceI egPHIs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QGV GdHjGf MJi ZOkG ddage ai bgQ YfGf hLYd GdBOGH QhVkG RGgQ hfhQ GdCMdGe s
(3BNQgG (B:s
(3hcGf HOG GdfXe JGSY YTQ eMQe jhe GdNejS ai GdSMQ ef YGe SJI ceG bO TQMfG hGdMeO ddg Ydi eG efMfG fLRJ GdCQLhRI HMeO Gddg JYGdi hUdi Gddg Ydi SjOfG hfHjfG hehdGfG eMeO Udi Gddg Ydjg hYdi Bdg hUMHg hSde JSdjekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B4 - (3U (B678s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(288/7) s
Keywords: (3GdYQhV hGdbhGais